Validation of the Lymphedema Life Impact Scale Version 2: A Condition-Specific Measurement Tool for Persons With Lymphedema. Issue 1 (January 2018) - Weiss, Jan; Daniel, Todd
Abstract : Background: Evidence-based practice supports the use of validated outcome measures to assess the effect of lymphedema; however, condition-specific lymphedema assessment measures are needed. The Lymphedema Life Impact Scale (LLIS) has been validated as a comprehensive lymphedema-specific instrument to assess the effects of lymphedema in any extremity. Objectives: This multicenter, cross-sectional study investigated the reliability and validity of a revised version of the LLIS, known as LLIS version 2. Methods: Qualifying patients from lymphedema clinics across the United States completed self-report outcome measures; clinicians measured limb circumference. Test-retest reliability was assessed in a subgroup of 21 participants. Internal consistency and validity were assessed in 84 participants with upper- or lower-limb lymphedema. Results: Intraclass correlation coefficients for test-retest reliability ranged from 0.687 to 0.895. Cronbach α coefficients for internal consistency ranged between 0.847 and 0.953. Construct validity of the LLIS was upheld with symptoms but not with edema severity. The LLIS correlated from moderately to highly with most domains of the comparator LYMQOL (Lymphedema Quality of Life scale) used in this study. Minimal clinically important difference of the LLIS was 7.27; MDC95 was 12.74. Limitations: Despite adequate group sizes, the vast majority of participants were white females, so generalizations to male patients or to those of different races should be done cautiously. Conclusions: LLIS version 2 is a valid and reliable tool for the assessment of severity of impairment among patients with lymphedema.